Euroisation and Monetary Policy in Bosnia and Herzegovina – Situation and Perspectives - Imamović-Čizmić, Kanita (Maastricht 30: A Central European Perspective, 2025)
The Central Bank of Bosnia and Herzegovina is an independent monetary institution established by the Constitution of Bosnia and Herzegovina as the sole authority for conducting monetary policy at the state level. Its powers and organisational structure are regulated by the Constitution of Bosnia and Herzegovina (Annex 4 of the Dayton Peace Agreement) and the Law on the Central Bank of Bosnia and Herzegovina. In accordance with these acts, the Central Bank functions as a currency board, where theconvertible mark is officially tied to the euro (EUR). This paper provides an overview of the regulatory framework for the operation of the Central Bank of Bosnia and Herzegovina, presents the management of foreign reserves and mandatory reserves, and discusses the suitability of the currency board in Bosnia and Herzegovina, which has led to a semi-official euroisation, facilitating the path to EU membership. Keywords: currency board, euroisation, Central Bank of Bosnia and Herzegovina